2021
DOI: 10.3390/molecules26175117
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Ultrasound Coupled with High-Pressure Technologies: Impact of Hybridized Techniques on the Recovery of Phytochemical Compounds

Abstract: The coupling of innovative technologies has emerged as a smart alternative for the process intensification of bioactive compound extraction from plant matrices. In this regard, the development of hybridized techniques based on the low-frequency and high-power ultrasound and high-pressure technologies, such as supercritical fluid extraction, pressurized liquids extraction, and gas-expanded liquids extraction, can enhance the recovery yields of phytochemicals due to their different action mechanisms. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 94 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…The cavitation forces of ultrasound can be used to break down polysaccharides. In particular, high-intensity ultrasound with high power (10-1,000 Wcm −2 ) and low frequencies (10-100 kHz) is suitable for M W reduction of carbohydrates (Feng et al, 2011;Zabot et al, 2021). In this process, cavitation bubbles expand to a size where their implosion generates strong shear forces.…”
Section: Introductionmentioning
confidence: 99%
“…The cavitation forces of ultrasound can be used to break down polysaccharides. In particular, high-intensity ultrasound with high power (10-1,000 Wcm −2 ) and low frequencies (10-100 kHz) is suitable for M W reduction of carbohydrates (Feng et al, 2011;Zabot et al, 2021). In this process, cavitation bubbles expand to a size where their implosion generates strong shear forces.…”
Section: Introductionmentioning
confidence: 99%
“…Like CAPE, ARC also activated tumor suppressor activity in p53 by abrogating its complex with mortalin [ 33 ]. Several studies have demonstrated the supercritical extraction that uses high pressure, low temperature, and allows reduction in organic solvents as a preferred method of extraction for retaining sensitive natural bioactive compounds [ 34 , 35 ]. Supercritical extracts have been shown to retain aroma as well as bioactive profile that closely resembles the original source [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the inefficiencies reported from a single application of ultrasound, new techniques involving ultrasound with accompaniments, such as thermosonication [58] and pressure (manosonication) [59], have been devised to provide food products with a more stable shelf life. Ultrasonication and ultrasonic homogenization use high-frequency acoustic waves [60] for laboratory and industrial applications.…”
Section: Ultrasound Technologymentioning
confidence: 99%